Biobased Construction from Agricultural Crops: Paper 1 - A State of Play of Commercial Solutions in Europe - Daly, Patrick; Barril, Paula G. (International Journal of Architectural Engineering Technology, 2024)
In response to environmental concerns and the global warming issue in particular there is a growing drive to decarbonise the building sector and transition it to more circular practices. Biobased construction materials, products and systems are an important low carbon and circular strategy as they can enable low to negative carbon construction and have strong circularity advantages notably being able to enter the bio cycle, using renewable, low to zero toxic resources and provide a range of other performance benefits, including moisture and vapour regulation. This novel research presents a unique state of play on the commercial application of biobased construction from selected agricultural crops, straw, miscanthus and hemp, focused on the European context. A desk-based review of known biobased material producers and manufacturers is undertaken, supplemented with semi structured interviews and site visits, to provide a comprehensive overview of the sector and detailed account of the types of biobased materials, products and systems that are being applied in buildings across Europe and beyond. The findings show that a diversity of agricultural crops are being utilised at different process, manufacture and construction technology levels, providing a range of tested and certified materials and products for application in mainly timber frame construction, but also some masonry solutions, and a growing number of modular systems. These operate in a diversity of supply chains and are being applied in a wide range of building types, both domestic and non-domestic, including multi story and complex buildings.